Darul Fikri as a Qur’an Science Boarding School Model: Darul Fikri sebagai Model Sekolah Asrama Ilmu Al-Qur'an - Aisah, Uswatun; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Pesantren are foundational in Indonesian Islamic education, shaping morally upright and knowledgeable generations, yet face challenges in adapting to rapid technological and global changes. Specific Background: Darul Fikri (DAFI) aims to integrate Qur’anic values with modern science, particularly STEM, to produce graduates competent in both spiritual and scientific domains. Knowledge Gap: Previous studies have explored Al-Qur’an integration in learning, but few offer a comprehensive model combining Qur’anic sciences, digital literacy, and international standards within pesantren education. Aims: This study proposes a strategic development plan for DAFI (2025–2034) to establish it as a leading Al-Qur’an Science Boarding School. Results: Mixed-method analysis (literature review, interviews, FGDs, SWOT) identified strengths in human resources and infrastructure, challenges in curriculum integration and digital literacy, and opportunities for international collaboration. Novelty: The plan introduces an integrative Al-Qur’an Science curriculum, digital literacy enhancement, global partnership programs, and holistic character development rooted in Qur’anic and national values. Implications: The model provides a replicable framework for modern pesantren to prepare globally competent, spiritually grounded leaders, bridging tradition with 21st-century educational demands. Highlights: Comprehensive integration of Al-Qur’an and STEM learning. Strengthening digital literacy through e-learning and labs. Holistic character and global competency development for santri. Keywords: Al-Qur’an Science, Pesantren Development, Digital Literacy, Holistic Education, STEM Integration